Prevalence of Trichinella larvae and extra-intestinal nematodes in Norwegian red foxes ( Vulpes vulpes) - Davidson, Rebecca K.; Gjerde, Bjørn; Vikøren, Turid; Lillehaug, Atle; Handeland, Kjell (Veterinary parasitology, 2006)
A survey of the parasitic fauna of the Norwegian red fox ( Vulpes vulpes) population was carried out in 1994/1995 and 2002–2005. All foxes were killed during the licensed hunting season from October to April and, in total, 393 animals from all regions of the country were examined. The present study details the results of extra-intestinal nematode and Trichinella larvae examinations. All individuals were examined for Trichinella, using routine digestion methods. Parasitological examination of the internal organs of some of the foxes also identified a number of different extra-intestinal nematodes. The following prevalences were identified (number positive/number foxes examined): Trichinella larvae 19/393 (4.8%); Capillaria böhmi ( C. böhmi) 88/174 (51%); Capillaria aerophila ( C. aerophila) 160/181 (88%); Crenosoma vulpis ( Cr. vulpis) 105/181 (58%) and Capillaria plica ( C. plica) 81/154 (53%). No evidence of Angiostrongylus vasorum infection was found. The 19 different Trichinella isolates were species typed by PCR and sequence analysis; 18 isolates were identified as Trichinella nativa and one as Trichinella britovi. A wide geographical distribution of the parasites was seen. The following exceptions were recorded: C. böhmi, the prevalence of which was significantly lower in northern Norway (6%) compared to other regions (central Norway, eastern Norway and southern and western Norway; 52–57%). There was a significantly higher prevalence of Trichinella infection in eastern Norway (8.1%), when compared with the rest of the country (0.6%). Cr. vulpis prevalence was significantly higher in central Norway (83%) than in other regions (41–56%). There were no significant differences in age and sex distribution of the parasites with the exception of Cr. vulpis where juvenile foxes had a greater likelihood of infection. The data also indicated that adult foxes were more commonly infected with Trichinella larvae (5.8%) than juveniles (3.3%) (no statistical significance).